Ruang sosial baru perempuan Tionghoa : sebuah kajian pascakolonial - Lim, Sing Meij (Jakarta : Yayasan Obor Indonesia, 2009)
On discrimination against Chinese Indonesian women
Revision of the author's thesis (doctoral)--Universitas Indonesia, 2008
Includes bibliographical references (p. 193-208) and index
In Indonesian, with summary in English
Keywords: Chinese -- Indonesia; Women -- Indonesia; Race discrimination -- Indonesia; Peranakan (Asian people) -- Race identity -- Indonesia